RETORIKA FOTOGRAFIS PADA KARTU POS LAMA (1890-1940) YANG BERTEMA PEKERJA DI JAWA - Kusrini Kusrini (Institut Seni Indonesia Yogyakarta, 2020)
Photographic Rhetoric On Old Postcards 1890-1940. Photographic rhetoric is a form of visual communication in an attempt to persuade through the medium of photography. It is usually found in photo works intended for promotion. One interesting medium to review with a photographic rhetorical perspective is the old (old-fashioned) postcard. In the early 19th century, postcards became a trend everywhere including in Indonesia (Dutch East Indies, then). The function of postcards to exchange news or short messages is also carried by another purpose, namely the promotion of colonial government occupied territory. This raises a question about how to persuade through the media photos on postcards. Data collection using purposive sampling method with postcard imaginary population in the book